Changing Patterns in Process Management and Improvement: Using RPA and RDA in Non- Manufacturing Organizations - Baranauskas, Gedas (European Scientific Journal, ESJ, 2018)
Being, from the first sight, a complementary part of process management within an organization, process management automation draws a very broad and promising perspective to the whole business field since it is a step closer to the smarter and next level efficiency. Therefore, this particular theoretical scientific research elaborates the topic of the application of Robotic Process Automation (RPA) and Robotic Desktop Automation (RDA) concepts within the work activities in non-manufacturing organizations as this is a non-widely examined area and offers the whole specter of opportunities. Therefore, focuses are based on process management in organizations where client service is key activity and direction with soft systems and operations used as working tools. In addition, a comparative analysis of key similarities and differences of terms and practical application of RPA/RDA within the manufacturing and non-manufacturing sector is provided. Problematic areas, which this particular topic escalates, have a wide framework: first, it is noticed that the scientific field regarding the application of RPA and related concepts in combination with other process management methods (for example, Lean, Agile or Business Process Management (BPM)) has not been widely discussed. Second, in generally most of the past and ongoing scientific researches and practices tendencies and problems in process automation within the manufacturing sector field have been investigated. Accordingly, it is missing both quantitative and qualitative analyses of past and current situations in non-manufacturing business and public organizations. To generalize, it is agreed that process automation has made a notorious impact not only on the tendencies of process management within the business field but also on a society as a human resource. Therefore, investigation of this topic as a very relevant subject is essential since it has a direct and very strong impact on business cycles, technological evolution, and job market.